MODERN VIEWS ON ETHIOPOLOGICAL FACTORS OF THE DEVELOPMENT OF TEMPOROMANDIBULAR JOINT DISORDERS (LITERATURE REVIEW) - V.F. Makeiev; M.Y. Oliynyk (Український стоматологічний альманах, 2018)
In the analysis of literature devoted to the temporomandibular joint, attention is concerned with differentiation of etiological factors and variants of the mechanism of development of TMD’s which were proposed by various authors. These disorders are due to peculiarities of the structure and function of the TMJ. Occlusion is the first and perhaps the most controversial etiological factor in the occurrence of TMD. The price was also important reason for temporomandibular disorders. Nowadays, most researchers include occlusion to the factors associated with the development of TMD, which plays possible role both in the tendency and in preserving TMD. Angle and others of their studies determined the effect of pathological dentition on the development of temporomandibular joints . The authors found that in patients with TMD, the difference between the height of central occlusion and the height of physiological rest was higher than in patients without TMD. Summarizing the results of the study, the authors have established a close relationship between pathological erosion of teeth and the appearance of temporomandibular dislocation. Discussions about the effect of occlusion on TMD have been influenced and limited by therapeutic measures in the occurrence of TMD, but modern researchers work to isolate the multifactorial etiology of temporomandibular disorder and reduce the role of occlusion as the main etiological factor in the onset of TMD.